The Relationship between Brachycephalic Head Features in Modern Persian Cats and Dysmorphologies of the Skull and Internal Hydrocephalus - Schmidt, M. J.; Kampschulte, M.; Enderlein, S.; Gorgas, D.; Lang, J.; Ludewig, E.; Fischer, A.; Meyer-Lindenberg, A.; Schaubmar, A. R.; Failing, K.; Ondreka, N.; Justus Liebig University Giessen (My University, 2017)
Background: Cat breeders observed a frequent occurrence of internal hydrocephalus in Persian cats with extreme brachycephalic head morphology. Objective: To investigate a possible relationship among the grade of brachycephaly, ventricular dilatation, and skull dysmorphologies in Persian cats. Animals: 92 Persian-, 10 Domestic shorthair cats. Methods: The grade of brachycephaly was determined on skull models based on CT datasets. Cranial measurements were examined with regard to a possible correlation with relative ventricular volume, and cranial capacity. Persians with high (peke-face Persians) and lower grades of brachycephaly (doll-face Persians) were investigated for the presence of skull dysmorphologies. Results: The mean cranial index of the peke-face Persians (0.97 ± 0.14) was significantly higher than the mean cranial index of doll-face Persians (0.66 ± 0.04; P < 0.001). Peke-face Persians had a lower relative nasal bone length (0.15 ± 0.04) compared to doll-face (0.29 ± 0.08; P < 0.001). The endocranial volume was significantly lower in doll-face than peke-face Persians (89.6 ± 1.27% versus 91.76 ± 2.07%; P < 0.001). The cranial index was significantly correlated with this variable (Spearman´s r: 0.7; P < 0.0001). Mean ventricle: Brain ratio of the peke-face group (0.159 ± 0.14) was significantly higher compared to doll-face Persians (0.015 ± 0.01; P < 0.001). Conclusion and Clinical Relevance: High grades of brachycephaly are also associated with malformations of the calvarial and facial bones as well as dental malformations. As these dysmorphologies can affect animal welfare, the selection for extreme forms of brachycephaly in Persian cats should be reconsidered.
Keywords: Brachycephaly; Breeding; Coronal craniosynostosis; Hydrocephalus; Magnetic resonance imaging; ddc:630